The role of lattice vibration in the terahertz region for proton conduction in 2D metal–organic frameworks. Issue 6 (3rd January 2020) - Itakura, Tomoya; Matsui, Hiroshi; Tada, Tomofumi; Kitagawa, Susumu; Demessence, Aude; Horike, Satoshi
Abstract : Terahertz-regime vibrations of 2D MOFs dominate the intrinsic proton conductivity, and the motions depend on the valence electronic structures. Abstract : We studied the relationship between proton conductivity and the terahertz-regime vibrations of two-dimensional MOFs. The results of spectroscopy studies clarified the essential role played by the collective motions in the terahertz region in 2D layers for efficient H + conduction. Ab initio calculations suggested the collective motion to be predominantly determined by the valence electronic structure, depending on the identity of the metal ion.